The Influence Of Product Attributes And Direct Marketing On Purchase Decisions Of Customers Of PT. Bank Central Asia KCP (Sub-Branch Office) Surabaya Street Medan - Shella; Aidil Putra; Thomas Sumarsan Goh (Enrichment : Journal of Management, 2022)
PT. Bank Central Asia is one of the largest private banks in Indonesia which was founded in 1957 which is managed directly by the Djarum Group. The development of BCA in Medan is also considered to be very significant so that it requires various assistance in establishing sub-branches so that the entire community can provide the facilities provided by the company and one of them is: Bank Central Asia, Surabaya road sub-branch. There was a decrease in the number of new customers, both those who opened savings or who applied for credit, which were obtained by PT. Bank Central Asia KCP Jalan Surabaya Medan. Weaknesses in the product attributes offered by the company. The implementation of direct marketing by employees of KCP Jalan Surabaya is rare because many customers from KCP Jalan Surabaya inform employees never to offer products over the phone because it is considered to interfere with customer activities every day. This research uses quantitative descriptive research. The total population in the study was 114 customers with the sampling technique using the Slovin formula, obtained as many as 89. Simultaneously there is a significant influence between product attribute variables and direct marketing on the purchasing decisions of PT. Bank Central Asia KCP Jalan Surabaya. While partially found product attribute variables have a significant effect on customer purchasing decisions PT. Bank Central Asia KCP Jalan Surabaya. Partially found direct marketing variables have a significant effect on customer purchasing decisions PT. Bank Central Asia KCP Jalan Surabaya. The results of this study indicate that direct marketing variables have more influence than product attributes on the purchasing decisions of PT. Bank Central Asia KCP Jalan Surabaya.